Handbook of Asian Criminology - Liu, Jianhong; Hebenton, Bill.; Jou, Susyan; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
With many of its countries undertaking development and modernization--and others taking major roles on the global stage--Asia is a region in flux. And as with any area in transition, there are myriad opportunities for crime to flourish. But at the same time that illegal activities are on the rise, so is the emergence of robust crime research in the region. The Handbook of Asian Criminology analyzes illicit enterprises and criminal justice efforts across a vast and varied continent. Contributions represent countries familiar in the West (Japan, Taiwan) and less known (Cambodia, Malaysia), and crimes examined range from the typical (homicide, drug trafficking) to the timely (human trafficking, insurance fraud, intellectual property crime). Expert studies of victims, of criminals as cultural icons, of the rise of the restorative justice movement, and of criminology itself demonstrate why Asia is viewed as a vanguard by colleagues elsewhere in the world. Among the topics covered: Cybercrime in Asia: trends and challenges. Curbing corruption and enhancing trust in government: lessons from Singapore and Hong Kong. Development of criminology in Japan: a sociological perspective. Contemporary crime and punishment in Thailand. Victims of domestic violence in India: do they have rights? Evolution of restorative justice for juvenile offenders in the People's Republic of China. The Handbook of Asian Criminology is a groundbreaking volume for researchers in criminology and criminal justice, particularly with an interest in the fields in Asia, as well as those in related disciplines such as sociology and international studies.
Keywords: Social sciences; Political science; Criminology; Social Sciences; Criminology & Criminal Justice; Political Science; Electronic books